Impact of stressful life events on central adiposity in the Pelotas Birth Cohort - Pamela J Surkan; Kwame S Sakyi; Alice Hu; Maria T Olinto; Helen Gonçalves; Bernardo L Horta; Denise P Gigante (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To investigate how stressful life events and social support relate to central adiposity in Southern Brazil. METHODS: Data included information from 802 participants in the 1982 Pelotas Birth Cohort that was collect in 2004-2005 and 2006. Stratifying by sex, we studied self-reported stressful life events during the year before 2004-2005 in relation to change in waist circumference between 2004-2005 and 2006 and waist-to-hip ratio in 2006, using both bivariate and multivariate linear regression models. RESULTS: In adjusted models, the experience of stressful life events during the year before 2004-2005 predicted a change in waist circumference in 2006 in men and a change in both waist-to-hip ratio in 2006 and waist circumference between 2004-2005 and 2006 in women. Men who experienced two or more stressful events had on average a one centimeter increase in their waist circumference between 2004-2005 and 2006 (β = 0.97, 95%CI 0.02-1.92), compared to those reporting no stressful events. For women, those who had one and those who had two or more stressful life events had over a 1 cm increase in their waist circumference from 2004-2005 to 2006 (β = 1.37, 95%CI 0.17-2.54; β = 1.26, 95%CI 0.11-2.40, respectively), compared to those who did not experience any stressful event. For both sexes, social support level was not significantly related to either waist-to-hip ratio or change in waist circumference, and it did not modify the association between stress and central adiposity. CONCLUSIONS: The experience of more than one stressful life event was associated with distinct indicators of central adiposity for men versus women.